Removal of vanadium from wastewater by multi-walled carbon nanotubes. Issue 3 (4th March 2017) - Yu, Yaqi; Wei, Qingqing; Li, Jinxin; Yang, Jinyan
ABSTRACT: Nitric acid heating reflux modified multi-walled carbon nanotubes (HMWCNTs) were used for the removal of vanadium(V) in aqueous solution. The removal rate of vanadium(V) decreased with the increase of the initial vanadium(V) concentration and the solution pH, and increased with the increase of reaction time, HMWCNTs amount and solution temperature. The adsorption equilibrium and dynamic kinetics fitted the Langmuir adsorption isotherm and pseudo-second order models. The results obtained by scanning electron micrography and Fourier transform infrared spectroscopy analysis revealed that the hydroxyl and carboxyl functional groups are mainly responsible for the vanadium adsorption. This study showed that the HMWCNTs proved to be a considerable adsorbent for the removal of vanadium from wastewater.